THE INFLUENCE OF COOPERATIVE LEARNING STRATEGY THINK PAIR SHARE AND INTEREST IN LEARNING ON ISLAMIC RELIGIOUS EDUCATION RESULTS OF JUNIOR HIGH SCHOOL - Imron Gunawan; Rusydi Ananda; Muhammad Rifai (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2020)
The purpose of this study was to determine the effect of implementing think pair share cooperative learning strategies and learning interest on learning outcomes of Islamic  Education. This research method is a quasi experiment. The study population was all grade V students spread over 3 classes. The sampling technique used was cluster random sampling. The data collection instruments were questionnaires and tests. The data analysis technique used was two-way analysis of variance in the α = 0.05 test. The results showed: (1) the average learning outcomes of students taught with the TPS learning strategy were higher than the average learning outcomes of students taught with expository learning strategies, (2) the average learning outcomes of Islamic Education for students with high learning interest  were higher than those for students with low learning interest, and (3) there is an interaction between learning strategies and interest in learning.